Legalization of Deed of Establishment of Limited Liability Company Fintech Without Permit from Financial Services Authority (OJK) - Dwiyanto, Sultan Alvaro; Alfi Taufiq Asyidqi (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
Fintech companies engaging in crowdfunding services based on information technology (LPBBTI) are required to establish a deed of incorporation as a limited liability company (PT) through a notary and obtain a license from the Financial Services Authority (OJK). However, there is a phenomenon where fintech companies that are already established as PTs operate without a license from OJK. The primary issue to be analyzed is the legal consequences on the validity and existence of the incorporation deed that has been created by the notary and whether it can be revoked or erased due to the company being classified as ilegal. The research approach used in this study is a normative juridical approach, focusing on the use of secondary data as references, with qualitative data as the type of data employed. The establishment of a PT is a requirement from OJK that must be fulfilled by fintech companies. For fintech companies that engage in LPBBTI activities without a business license, criminal sanctions can be imposed. Additionally, the notary is not obligated to ensure that the fintech company has obtained a business license from OJK. The deed of incorporation of the PT remains legally valid, even if the fintech company does not have a business license from OJK, because the incorporation deed serves as evidence that the PT is registered as a legal entity, and it does not result in the annulment or removal of the deed of incorporation.